Koszty działalności badawczo-rozwojowej w przedsiębiorstwach województwa podkarpackiego na podstawie badań ankietowych - Pydo, Sabina (Research and Development Costs in Companies Based in the Podkarpacie Province on the Basis of Questionnaire Researches, 2006)
The main aim of this article is to present the results of questionnaire researches conducted in forty seven companies from Podkarpacie which run the research and development activity. The analysis of the researches results makes possible to asses areas in which the firms conduct R&D activity, the way they record costs of R&D activity and answer the question if the firms have a system of costs accounting to manage R&D.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 353-359